2020
DOI: 10.1038/s41598-019-56894-x
|View full text |Cite
|
Sign up to set email alerts
|

In silico analysis of alternative splicing on drug-target gene interactions

Abstract: full-length protein-coding transcripts, highlighting the complexity of the total proteome that can be expressed by different cells and tissues in the human body. Numerous studies have noted the functional importance of maintaining a coordinated regulation of alternative events in various biological processes, such as tissue development and aging 7-9. Isoforms of a gene often appear to have different, sometimes even opposite functions, and are tightly regulated to express in a context-specific manner. Conversel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 77 publications
(51 reference statements)
0
6
0
Order By: Relevance
“…At least 75% of human protein-coding genes give rise to multiple distinct protein isoforms 2 , which can severely affect the sensitivity of therapeutic targeting of specific proteins. In a recent study of 883 small molecule cancer drugs targeting 1,434 different proteins, the authors found that 76% of these drugs would miss a target isoform if a switch occurred, or induce off-target effects in isoforms expressed in normal tissues 3 . Because isoforms of a protein may be differentially expressed in individual cancer cells 4 , they may produce a pool from which escape variants can arise when selective pressure is exerted by targeted therapy.…”
Section: Main Textmentioning
confidence: 99%
“…At least 75% of human protein-coding genes give rise to multiple distinct protein isoforms 2 , which can severely affect the sensitivity of therapeutic targeting of specific proteins. In a recent study of 883 small molecule cancer drugs targeting 1,434 different proteins, the authors found that 76% of these drugs would miss a target isoform if a switch occurred, or induce off-target effects in isoforms expressed in normal tissues 3 . Because isoforms of a protein may be differentially expressed in individual cancer cells 4 , they may produce a pool from which escape variants can arise when selective pressure is exerted by targeted therapy.…”
Section: Main Textmentioning
confidence: 99%
“…While the genetic code explaining how DNA is translated into proteins is universal, the regulatory code that determines when and how the genes are expressed varies across different celltypes and organisms (2). Same cis-regulatory elements (CREs) often have distinct functions and activities in different biological contexts, while widely spaced multiple CREs may cooperate, resulting in context-dependent use of alternative promoters with varied functional roles (3)(4)(5)(6). Such observations suggest existence of polysemy and distant semantic relationship within sequence codes, which are key properties of natural language.…”
Section: Introductionmentioning
confidence: 99%
“…We analyzed the structures of some of the transcripts and found that some contain targeting domains of the drugs, while many of them do not. Some studies have found that splicing-regulated protein isoforms are closely related to drug evaluation [ 28 , 29 ], but more functions of the transcripts remain to be further explored.…”
Section: Discussionmentioning
confidence: 99%